Assessment of International NGOs' Roles and Challenges in Peacebuilding in Northeast Nigeria - Saka, Adedotun Jamiu (Journal of Governance, 2025)
Non-Governmental Organizations (NGOs) have been one of the non-state actors that have contributed to world peace and peaceful coexistence; NGOs have served as a platform for individuals and organizations to contribute to peacebuilding and resolve various humanitarian crises. Every part of the world has its peculiarities; hence, it becomes imperative for international NGOs to face various challenges while discharging their duties. This paper focuses on identifying the roles and impediments of international NGOs in peacebuilding in the northeastern region of Nigeria. This paper adopted a qualitative research method, and the qualitative data was collected through journals, research publications, websites, and textbooks. The data collected reveals that illiteracy, insecurity, customs, and traditional beliefs, among other factors, are impediments that hinder the operations of international NGOs in the Northeast Region of Nigeria. This paper also identifies the roles of international NGOs in peacebuilding; education and research, provision of relief materials, provision of health care, and provision of social amenities are some of the roles of international NGOs identified in this paper. This paper suggested that the government should invest more in the education sector or adopt the United Nations Educational, Scientific and Cultural Organization's (UNESCO) education funding policy, and NGOs should partner with traditional rulers, as they are the custodians of traditions and customs, to ensure proper implementation of their policies and execution of their programs.